2019
DOI: 10.1002/jssc.201900462
|View full text |Cite
|
Sign up to set email alerts
|

The experimental design approach to the optimization of a simple quick easy cheap effective rugged and safe method for the analysis of phytoestrogens in complex soy‐based food

Abstract: The present paper deals with the multivariate optimization of an extractionpurification strategy for the determination of phytoestrogens (daidzein, genistein, coumestrol, formononetin, and biochanin A) in soy-based meat substitutes by high performance liquid chromatography with tandem mass spectrometry. For a reliable quantitation of these new concerning compounds in such a complex matrix, recovery and matrix effect must be carefully evaluated. Therefore, two sequential experimental designs were used to optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It was reported that about 50 homoisoflavoniods were purified and identified by repeated column fractionations [1]. HPLC with diode array detector (DAD) and MS/MS has been developed for rapid isolation and characterization of bioactive components from complex natural products [8–11]. However, information about comprehensive analysis of homoisoflavonoids, especially for minors, in O. japonicus by HPLC–DAD–MS/MS is restricted because of the existence of multicomponents, restriction of detection sensitivity, and coelution of minor and abundant compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that about 50 homoisoflavoniods were purified and identified by repeated column fractionations [1]. HPLC with diode array detector (DAD) and MS/MS has been developed for rapid isolation and characterization of bioactive components from complex natural products [8–11]. However, information about comprehensive analysis of homoisoflavonoids, especially for minors, in O. japonicus by HPLC–DAD–MS/MS is restricted because of the existence of multicomponents, restriction of detection sensitivity, and coelution of minor and abundant compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%